Pengaruh Penyemprotan Daun Sirih dan sodium Hipoklorit Pada Cetakan Elastomer Terhadap Perubahan Dimensi - M Zulkarnain; Sarah Devina (Jurnal Material Kedokteran Gigi, 2016)
Elastomer is often used to make an impression. In prosthodontics, impression material that have been exposed to infected saliva pose a main source of cross contamination in dental office and laboratories, therefore desinfection of impression is recommended by American Dental Association (ADA) to prevent possible transmission of infectious diseases. Piper betle L. 25% and sodium hypochlorite 0,5% can both be used as desinfection agent by spraying the impression materials. But some desinfection process can effect the dimensional accuracy of the impressions materials especially the hidrophilic materials. The aim of this study was to determine the influence of spray desinfection with piper betle L. 25% and sodium hypochlorite0,5% on dimensional accuracy of cast made by elastomeric impression materials. Type of this research was a laboratory experiment. The samples of this research were the cast made by elastomeric impression materials, two abutment preparations in shape with diameter (buco lingual)6.33 mm, height (occluso gingival) 8.02 mmand distance between the centers of the abutments 28.25 mm and total samples were 30 for 3 groups. The cast dimension was measured using digital caliper and dimensional accuracy test was analyzed with T-Independent test. The result showed that there was a statisticallyinfluence of spray desinfection with piper betle L. 25% and sodium hypochlorite0,5% on dimensional accuracy of cast made by elastomeric impression materials(p<0.05) and the percentage of the dimensional change is in normal range recommended by ADA 19 (<0,5%). Therefore, spray desinfection with piper betle L. 25% can be used in elastomeric impression materials.